2011
DOI: 10.1124/jpet.111.183004
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of GGsTop, a Novel and Selective γ-Glutamyl Transpeptidase Inhibitor, on Ischemia/Reperfusion-Induced Renal Injury in Rats

Abstract: GGsTop [2-amino-4-{[3-(carboxymethyl)phenyl](methyl)phosphono}butanoic acid], is a novel, highly selective, and irreversible ␥-glutamyl transpeptidase (GGT) inhibitor with no inhibitory activity on glutamine amidotransferases. In this study, we investigated the effects of treatment with GGsTop on ischemia/reperfusion-induced renal injury in uninephrectomized rats. Ischemic acute kidney injury (AKI) was induced by occlusion of the left renal artery and vein for 45 min followed by reperfusion 2 weeks after contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…This might represent an inflammatory response occurring as a sequelae of ischaemia and shortage of oxygen supply. Similar observations were previously reported by researchers who demonstrated the presence of hyaline exudation in the interstitial spaces as well as peritubular congestion (32). Although reperfusion is essential for the survival of ischaemic tissue, there is good evidence that reperfusion itself causes additional cellular injury "reperfusion injury", which has been attributed to the generation of reactive oxygen species (ROS), depletion of ATP, neutrophil infiltration, and membrane lipid alterations, cytoskeletal dysfunction and intracellular Ca 2+ accumulation (27).…”
Section: Discussionsupporting
confidence: 74%
“…This might represent an inflammatory response occurring as a sequelae of ischaemia and shortage of oxygen supply. Similar observations were previously reported by researchers who demonstrated the presence of hyaline exudation in the interstitial spaces as well as peritubular congestion (32). Although reperfusion is essential for the survival of ischaemic tissue, there is good evidence that reperfusion itself causes additional cellular injury "reperfusion injury", which has been attributed to the generation of reactive oxygen species (ROS), depletion of ATP, neutrophil infiltration, and membrane lipid alterations, cytoskeletal dysfunction and intracellular Ca 2+ accumulation (27).…”
Section: Discussionsupporting
confidence: 74%
“…GGsTop covalently binds between the side chain oxygen of Thr-381 of human GGT1 (hGGT1) and the phosphate of GGsTop, resulting in an enzyme-inhibitor complex (28). Yamamoto et al (33) reported that no abnormalities were observed in general symptoms, body weight, and amount of food intake for 2 wk after intravenous administration of GGsTop at a single dose of 30 or 100 mg/kg body wt. Only less than 4% of the compound is hydrolyzed in neutral water over a month (33).…”
mentioning
confidence: 98%
“…In a variety of diseases, GGT1 is induced and mislocalized, resulting in cleavage of substrates in serum and in interstitial fluid, thereby contributing to the disease pathology. GGT1 activity has been shown to potentiate tissue damage in ischemia-reperfusion injury, to contribute to airway hyperreactivity in asthma, to initiate the metabolism of a series of glutathione-S-drug conjugates to nephrotoxins, and to increase resistance of tumors to alkylating agents (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%